A Modified Method for Finding Initial Basic Feasible Solution for Fuzzy Transportation Problems Involving Generalized Trapezoidal Fuzzy Numbers. Issue 1 (April 2021) - Uma Maheswari, P.; Vidhya, V.; Ganesan, K.
Abstract: In this paper, we propose a modified method for finding an initial basic feasible solution(IBFS) for fuzzy transportation problem(FTP) involving generalized trapezoidal fuzzy numbers(GTFNS). Without disturbing the fuzzy nature, using the parametric representation of fuzzy numbers, the optimal solution of the FTPP is obtained. A numerical illustration is given to demonstrate the suitability and efficiency of the proposed procedure and the solution is compared with the existing methods.